Assessment of non-standard employment as a factor of average per capita income - Atabayeva, A.K.; Pritvorova, T.P.; Simonov, S.G. (BUKETOV BUSINESS REVIEW, 2021)
Object: Purpose of this paper is to identify and assess the impact of non-standard employment on the income of the population in Kazakhstan. Methods: For this study, we used methods of statistical multiple correlation and regression analysis based on the software package “Data Analysis” offered by MS Excel. We used data from the official website of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the RK at stat.gov.kz. Findings: We have performed a preliminary selection of statistical indicators and determined a group of factors (and corresponding indicators) that hypothetically affect the population income for the period of 2004–2018. We have highlighted a total of twelve factors significantly affecting the income and grouped them into four groups: employment and income indicators, demographic and social indicators. Based on the selection of the most significant factors, we have constructed a regression equation that demonstrates the degree of influence on the resulting income indicator. Subsequently, we have assessed the obtained regression model. The regression equation found is significant by the Fisher criterion; all its parameters, including the intercept term, are significant by the Student’s criterion with a maximum error of 0.049. Autocorrelation of the residues is non-existent (according to the Durbin-Watson criterion). The multiple correlation coefficient is 0.99. The results obtained can be useful for assessing the effectiveness of various social policy instruments, both at regional and national levels. Conclusions: Indicators of employment, average wages, and social benefits occupy an important place in the system of indicators of average per capita income. The analysis shows a strong positive relationship between these indicators. At the same time, the overall relationship between changes in indicators of non-standard employment and population incomes in the Republic of Kazakhstan appears to be important for a more adequate analysis of the situation. A negative correlation between indicators of non-standard employment and per capita income confirms the vulnerability and instability of non-standard employee labor relations, and receiving a lower income compared to standard employment.